The Description and Documentation of the Karonese Semantic - Rosita Ginting; Leman Sembiring; Joy Sembiring; Sugihana Sembiring (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2019)
The research, recording, and documentation of Karonese Semantic is an attempt to re-identify the types of word meaning, meaning relation, meaning change and meaning of names in Karonese. The semantics of Karo language is a type of communication that reflects the cultural values ??of the region, and is a part of the national culture. The Karonese sematic needs to be done in an attempt to recapture as clear information as possible about the types, relationships and changes in the meaning and meaning of names in Karonese. Semantics, which is a science of meanings of words, helps to answer it. To get research data in the form of descriptive qualitative, we applied an observation method with the technique of involment and communication, a method of interview with the recording and noting down technique, and a method of documentation with noting down technique. The results are presented in narrative form theory with structural analysis.